2020
DOI: 10.1016/j.pbb.2020.172906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcohol use on the adolescent brain and behavior

Abstract: Adolescence is a particularly vulnerable neurodevelopmental period marked by high rates of engagement with risky alcohol use. This review summarizes the cognitive and neural consequences following alcohol use during adolescence from longitudinal design studies in humans and animals. Findings from human adolescent studies suggest that binge drinking and heavy alcohol use is associated with poorer cognitive functioning on a broad range of neuropsychological assessments, including learning, psychomotor speed, att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
163
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(182 citation statements)
references
References 145 publications
5
163
0
14
Order By: Relevance
“…Over the past years, rodent models have been used to study alcohol's impact on adolescent brain and consequent behavioral impairments. Despite not fully recapitulating the complex human behavior defects, animal models provided findings partly consistent with human research (14, 18,23).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Over the past years, rodent models have been used to study alcohol's impact on adolescent brain and consequent behavioral impairments. Despite not fully recapitulating the complex human behavior defects, animal models provided findings partly consistent with human research (14, 18,23).…”
Section: Introductionsupporting
confidence: 59%
“…AAE is also believed to have deleterious effects on verbal learning and memory, and lead to long-lasting deficits on attentional and executive functions (14,16). Moreover, AAE significantly increases the risk of developing psychiatric and behavioral disorders later in life, including alcohol addiction (7,13,17,18), and studies have revealed a significant association between the age of drinking onset and the risk of developing alcohol dependence later in life (19,20). Altogether, it has become clear that, because of the high plasticity of the brain, adolescence is a very sensitive period for the development of alcoholrelated behavioral impairments.…”
Section: Introductionmentioning
confidence: 99%
“…These statistics are concerning because excessive alcohol use during adolescence is associated with a myriad of negative consequences including alcohol and substance use disorders (AUD, SUD; Dwyer‐Lindgren et al, 2018), and other mental health problems (Pompili et al, 2010; Teesson et al, 2010; Welsh et al, 2017). Alcohol use during adolescence has also been associated with alterations in brain structure and function, including aberrant activation patterns during response inhibition tasks (for review, see Lees et al, 2020; Lees et al, 2019; Squeglia and Cservenka, 2017; Squeglia and Gray, 2016), as well as poorer test performance across cognitive domains, with executive functions and memory being the most vulnerable (Gould, 2010; Lees et al, 2019). Recent longitudinal neuroimaging studies have begun investigating, and have shown, that underlying neural vulnerabilities of response inhibition in substance‐naïve children appear to contribute to earlier initiation and problematic progression of alcohol use during adolescence (Squeglia and Cservenka, 2017).…”
mentioning
confidence: 99%
“…Age at first full drink prior to 21 years (AFD<21) and subsequent binge drinking (BD) are two important factors linked to the development of alcohol use disorders (AUDs) (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Early onset of alcohol use may interfere with ongoing neurodevelopment, inducing neurobiological changes that could promote subsequent development of AUDs (1,2). Human neuroimaging studies indicate that early onset of alcohol use and BD in adolescents or emerging adults are linked to multiple brain structural changes (1,2), such as reduced cortical thickness (6), decreased surface area (7), and increased grey matter (GM) densities (8) in frontal regions, and a GM volume reduction in many regions (9)(10)(11) with exceptions including striatal volumetric increases (12). Sex-related effects have also been observed, with cortical thickness in selected frontal regions thinner in males and thicker in females (13) and putamenal volumes smaller in males and larger in females (14).…”
Section: Introductionmentioning
confidence: 99%